Potential source rocks in the western Kansas petroleum province - Hill, Tyler J. (Kansas State University, 2011)
The source of the hydrocarbons in western Kansas has been an ongoing debate for many years. The highly organic-rich Anadarko basin, directly south of western Kansas, has been a very prolific producer for many years. This basin is the most widely accepted source of the oil in Kansas, as it is very deep and thermally mature. The main source rock in this area is the Woodford Shale, a very thick, very organic-rich unit which has been proven to produce many hydrocarbons. Several studies have been done on the oils that are presently in Kansas, suggesting that they can be traced back to the source of the Woodford Shale. The hydrocarbons in the Anadarko basin would have traveled several hundred miles, which would require that the migration mechanism be unusually efficient. An alternate explanation could be that one of the many organic black shales in western Kansas may have sourced this oil. This study examines formations of Cambrian to Permian ages which include organic shales interbedded with several known producing formations. Shales of these ages in other areas have produced thermally mature hydrocarbons, which indicate relatively high temperatures and pressures. Several models suggest that thermal maturity may be reached even with lower temperatures if burial times are longer. The shales in western Kansas were deposited in marine seas, and upon TOC testing, proved to be very organic-rich. Two sets of data were analyzed in this study, with the first from northwestern Kansas, and the second from southwestern Kansas. These two sets were analyzed for TOC, whole-rock analysis, and vitrinite reflectance. The shales analyzed from the first set proved to be thermally immature. Had they been subjected to higher temperatures, then they would have made excellent source rocks. The second set of shales analyzed also proved to be thermally immature with the exception of a few deeper shales, which are closer to being mature source rocks. These shales may have contributed to some of the hydrocarbons currently within Kansas.
Keywords: potential; Source; Geochemistry (0996); Geology (0372)